Catalyst‐free synthesis of phytosterol diacid monoesters and their competitive effect on the solubilization of cholesterol in model bile mixed micelles. Issue 3 (12th February 2022) - Hu, Yuyuan; Ma, Chuanguo; Chen, Xiaowei; Bai, Ge; Guo, Shujing
Abstract : Abstract: Phytosterols have received an extensive attention owing to their excellent cholesterol‐lowering activity and the role in cardiovascular diseases prevention. Phytosterol diacid monoesters, the important intermediates in the structural modification of free phytosterols, were usually obtained by chemical method with catalyst. The aim of this research was to provide an eco‐friendly approach for the preparation of phytosterol diacid monoester and explore the possible mechanism of their hypocholesteremic effect using model bile mixed micelles. Catalyst‐free synthesis of β ‐sitosterol with succinic anhydride, maleic anhydride, and glutaric anhydride was investigated and optimized. The yields of three β ‐sitosterol diacid monoesters all reached above 94% under optimum reaction conditions and their chemical structures were confirmed further by mass spectroscopy, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. Compared with β ‐sitosterol, β ‐sitosterol diacid monoesters possessed the increased thermal stability (up to an above 355.28°C) and improved solubility in binary mixed micelle system (exceeding 1.7 mM) and similar cholesterol‐lowering activity (7.78%–11.05%). Moreover, β ‐sitosterol diacid monoesters showed the competitive effect on solubilization of cholesterol due to their enhanced micellar incorporation capacity. Overall, the competition with cholesterol in vitro gives useful information about the cholesterol‐lowering activity of phytosterol diacid monoesters, which will further expand their applications in the food industry and health. Practical Application: Modified phytosterols, phytosterol diacid monoesters, were successfully synthesized in petroleum ether without catalyst. These products enhanced the thermal stability of free phytosterols and reduced the dissolution capacity of cholesterol in model bile mixed micelles due to competitive solubilization. These results indicated that phytosterol diacid monoesters represented cholesterol‐lowering potential, which might further expand the applications in the food industry and health.